Electronic Medical Record System Using Ethereum Blockchain and Role-Based Access Control - Loh, Chee Ming; Chuah, Chai Wen (Applied Information Technology And Computer Science, 2021)
Medical record is a document that records the disease, diagnosis, and treatment history of patients. These records help the doctor to determine the diseases and provides patients drug prescriptions. However, there is a case about the falsification of medical records. The doctor falsified the medical record to evade legal responsibility. Also, according to 13abc Action news, some healthcare organizations found that employees unauthorized access to medical records. The employee accessed the medical records without work-related purpose but for their own benefit. Hence, this project intends to develop a web-based Electronic Medical Record system to solve the address the issues mentioned above. This system store the hash value of medical records in blockchain as a reference to prevent falsification of medical records. The system also implements access control to restrict unauthorized access to medical records. The methodology uses to develop the proposed system is Object-Oriented System Development (OOSD). Java is the main programming language uses to develop the system. The development of this system protects the confidentiality and integrity of medical records. This system may prevent falsification of medical records and restricts unauthorized access to medical records.